Non-Coding RNAs and Oral Cancer: Small Molecules With Big Functions - Erfanparast, Leila; Taghizadieh, Mohammad; Shekarchi, Ali Akbar (Frontiers in Oncology, 2022)
Oral cancer remains a major public concern with considerable socioeconomic impact in the world. Despite substantial advancements have been made in treating oral cancer, the five-year survival rate for oral cancer remained undesirable, and the molecular mechanisms underlying OSCC carcinogenesis have not been fully understood. Noncoding RNAs (ncRNAs) include transfer RNAs (tRNAs), as well as small RNAs such as microRNAs, and the long ncRNAs such as HOTAIR are a large segment of the transcriptome that do not have apparent protein-coding roles, but they have been verified to play important roles in diverse biological processes, including cancer cell development. Cell death, such as apoptosis, necrosis, and autophagy, plays a vital role in the progression of cancer. A better understanding of the regulatory relationships between ncRNAs and these various types of cancer cell death is therefore urgently required. The occurrence and development of oral cancer can be controlled by increasing or decreasing the expression of ncRNAs, a method which confers broad prospects for oral cancer treatment. Therefore, it is urgent for us to understand the influence of ncRNAs on the development of different modes of oral tumor death, and to evaluate whether ncRNAs have the potential to be used as biological targets for inducing cell death and recurrence of chemotherapy. The purpose of this review is to describe the impact of ncRNAs on cell apoptosis and autophagy in oral cancer in order to explore potential targets for oral cancer therapy.